Pembelajaran Interaktif Articulate Storyline 3: Peningkatan Minat dan Hasil Belajar IPA Materi Struktur Bumi - Hasanah, Uswatun; Firdaus, Thoha; Rosa Sinensis, Arini (U-Teach: Journal Education of Young Physics Teacher, 2025)
This research aims to find out how students' learning outcomes and interest in learning are influenced by involving Articulate Storyline 3-based learning media in science subjects on the structure of the earth. This research uses a nonequivalent control group design research methodology, namely there are two groups, the experimental class and the control class. Based on the results of research and data analysis regarding student learning outcomes, it was found that after using Articulate Storyline 3-based learning media, the comparison between the increase in learning outcomes for the experimental class and the control class proved that the average learning increase for the experimental class was higher than the control class, namely the average The N-gain of the control class is N-Gain 0.51 with medium qualifications and the average N-Gain of the experimental class is N-Gain 0.70 with medium qualifications. Furthermore, based on the results of the independent sample T-test analysis, the P value was obtained, namely 0.006 < 0.05, so it can be concluded that there is an influence of the use of interactive learning media based on Articulate Storyline 3 on student learning outcomes. And based on the results of research and data analysis regarding student interest in learning, it was found that after implementing the Articulate Storyline 3-based learning media, the qualifications for student interest in learning were very high, with an average of 89.24%. Because of this, the Articulate Storyline 3 learning media is suitable for use to increase student interest and learning outcomes.